Reconceiving barriers for democratic health education in Danish schools: an analysis of institutional rationales. Issue 1 (2nd January 2017) - Danielsen, Dina; Bruselius-Jensen, Maria; Laitsch, Daniel
ABSTRACT: Health promotion and education researchers and practitioners advocate for more democratic approaches to school-based health education, including participatory teaching methods and the promotion of a broad and positive concept of health and health knowledge, including aspects of the German educational concept of bildung . Although Denmark, from where the data of this article are derived, has instituted policies for such approaches, their implementation in practice faces challenges. Adopting a symbolic interactionist analytical framework this paper explores and defines two powerful institutional rationales connected to formal and informal social processes and institutional purposes of schools, namely conservatism and Neoliberalism. It is empirically described and argued how these institutional rationales discourage teachers and students from including a broad and positive concept of health, the element of participation, and the promotion of general knowledge as legitimate elements in health education. This paper thus contains a perspective on health education practice, which, in a new way, contributes to explain the relatively slow progress of democratic approaches to school health education.